ANALYSIS OF THE EFFECT OF SERVICE QUALITY, PRICE AND PERCEPTIONS OF RISK ONLINE SHOPPING AGAINST PURCHASE INTEREST IN E-COMMERCE CUSTOMERS PT. MATAHARI DEPARTMENT STORE TBK KUPANG BRANCH - Melkianus Teddison Bulan; Dr. Sukesi, MM (Universitas Dr. Soetomo, 2020)
The era of revolution 4.0 brought many conveniences in the field of marketing, both for producers and for consumers. Advances in technology and information in the field of marketing are referred to as e-commerce. Therefore, there are currently many online stores operating because of this convenience, one of which is Matahari.com/Matahari App. But behind this convenience, there are still losses or risks that need to be watched out for. The purpose of this study is to analyze and identify service quality, price and perception of risk simultaneously influencing the buying interest of e-commerce customers of PT. Matahari Department Store Tbk Kupang Branch, analyze and identify service quality, price and perceptions of risk partially affect the buying interest of e-commerce customers of PT. Matahari Department Store Tbk Kupang Branch and analyze and identify from service quality, price and perceptions of risk there is more dominating influence on buying interest of e-commerce customers of PT. Matahari Department Store Tbk Kupang Branch. The sampling technique used in this study was accidental sampling with a total sample size of 100 respondents. While the data analysis technique uses descriptive analysis, validity test, reliability test, classic assumption test, multiple linear regression analysis, hypothesis testing, dominant variable test and correlation coefficient test and multiple determination (R2). The results showed that simultaneously (F-test) all variables significantly influence together on online shopping interest on the Matahari.com/Matahari App site. Partially (t-test), service quality (X1), a negative and significant effect on online shopping interest (Y) on Matahari.com/Matahari App, while the variable price (X2) and perceptions of risk (X3) have a positive and significant to online shopping (Y) interest in Matahari.com/Matahari App. The most dominant variable influencing online buying interest (Y) is perceptions of risk (X3).